The structural and dielectric properties of Bi(Fe0.95Sm0.05)O3 ceramic. Issue 1 (17th February 2022) - Kumar, Nripesh; Shukla, Alok; Kumar, Nitin; Chaitanya, Pramod; Choudhary, R. N. P.
Abstract: This article exhibits that how a polycrystalline Bi(Fe0.95 Sm0.05 )O3 ceramic was synthesized using Solid-State-Reaction route technique. The structural and dielectric characteristic properties of the ceramic have also been studied. X-Ray Diffraction technique has been used for the identification of single-phase orthorhombic symmetry. It has been observed that the minor substitution of Samarium (i.e. Sm; a rare-earth element) at B-site in Bismuth ferrite (BiFeO3 ) suppresses the impurity section formation which is a basic disadvantage in BiFeO3 based ceramics. The grains were found homogeneously spread on the ceramic surface. The detailed investigations of grain and grain boundaries have delivered numerous interesting and useful outcome for the further device applications.